A new species of Dieida Strand, 1911 from Turkey (Lepidoptera: Cossidae) - Japaridze, Lasha-Giorgi; Hulsbosch, Ramon (Zootaxa, 2023)
In the article Dieida versicolor sp. nov. is described as a new species based on two specimens, one male and one female, from Okurcalar, Turkey. In this study taxonomic and distributional data available for the new species are also summarized.